Cultural Literacy : Ondel-Ondel Betawi in Elementary School Textbooks - Ummah, Wihdatul; Mudrika, Dadan; Fatmawati, Ayu Widya; Gumala, Yosi (Jurnal Basicedu, 2024)
This study aims to analyze the use of Betawi ondel-ondel in elementary school textbooks as a means of cultural literacy for students. The methodology used is a literature study that includes a review of elementary school textbooks that contain material about Betawi culture and the use of ondel-ondel in an educational context. The results showed that the use of ondel-ondel in elementary school textbooks made a positive contribution to students' understanding and appreciation of Betawi culture. Students not only gained knowledge about ondel-ondel, but also developed important cultural literacy skills. The conclusion of this study is the importance of integrating local cultural elements in the primary education curriculum to enhance students' understanding of their cultural heritage. The last recommendation from this study is the need for more research and development of teaching materials that utilize the potential of local culture as a means of learning in elementary schools